2000
DOI: 10.1161/01.hyp.35.1.413
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory Amino Acids in the Rostral Ventrolateral Medulla Support Blood Pressure in Spontaneously Hypertensive Rats

Abstract: Abstract-Injection of the excitatory amino acid (EAA) antagonist kynurenic acid (KYN) into the rostral ventrolateral medulla (RVLM) of anesthetized rats has no effect on arterial pressure. However, we recently reported that after inhibition of the caudal ventrolateral medulla, injection of KYN into the RVLM decreased arterial pressure to the same level as produced by complete inhibition of the RVLM. We have suggested that these results reflect tonically active EAA-mediated inputs to the RVLM producing both dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
119
4
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(135 citation statements)
references
References 15 publications
10
119
4
2
Order By: Relevance
“…Hypertensive rat models with enhanced angiotensinergic activation of the RVLM also appear to have augmented glutamatergic tone (3,19,20). However, in the present study we found no evidence to support the notion that enhanced tonic glutamatergic inputs to the RVLM raise SNA in the OZR.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…Hypertensive rat models with enhanced angiotensinergic activation of the RVLM also appear to have augmented glutamatergic tone (3,19,20). However, in the present study we found no evidence to support the notion that enhanced tonic glutamatergic inputs to the RVLM raise SNA in the OZR.…”
Section: Discussioncontrasting
confidence: 95%
“…In spontaneously hypertensive rats the tonic CVLM-mediated GABAergic inhibition of the RVLM appears to be attenuated (37). Furthermore, in many hypertensive rat models, tonic activation of RVLM by glutamate and angiotensin II are augmented (9,17,18,19,20). The principle observations of the present study are that 1) inhibition of the RVLM evoked a greater decrease in MAP in OZR compared with LZR; 2) antagonism of AT 1 Fig.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In renovascular hypertensive rats, as well as in SHRs (Ito et al 2000), Dahl salt-sensitive rats (Ito et al 2001) and rats used in an experimental model of pulsatile compression of the RVLM (Morimoto et al 1999), the blockade of excitatory amino acid receptors in the RVLM elicited profound decreases in the arterial pressure. Our hypothesis is that the increased glutamatergic activity in the RVLM seen in hypertension is in part mediated by local or circulating Ang II.…”
Section: The Rostral Ventrolateral Medulla and The Generation Of The mentioning
confidence: 99%